Yoga Helps to Improve Immunity & Fight Against Infection During Covid19 - Pravin Pande1 , Vaishali Tendolkar2 , Shaini Suraj3 , Ashish Anjankar4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Corona is a pandemic disease but other than the corona also so many viruses and organisms effect on therespiratory system and harm on immune system of the body. Yoga plays a important role in the life. Yoga,perhaps, is one amongst the foremost effective and tried resistance boosters that we will adopt for a healthierlife. Yoga could be a holistic follow that strengthens our body physically similarly as mentally. As a result,the body’s defense conjointly improves in such a condition. A healthy life may be simply achieved if wehave a tendency to learn to adopt a healthy modus vivendi, healthy food decisions and regular follow of yogaand meditation. Ayurveda, yoga, and meditation square measure the perfect factors to measure a healthy life.Surya Namaskar or Sun Salutation could be a sequence of twelve powerful yoga poses. Besides being anexcellent vas physical exercise, Surya namaskar includes all 12 asanas and it will help to the growth of thephysical body as well as mental peace. Surya Namaskar is additionally legendary to possess an associatevastly positive impact on the body and mind.